A new fuzzy multi-criteria decision making approach for municipal solid waste disposal options - Tarmudi, Zamali; Abdullah, Mohd Lazim; Md. Tap, Abu Osman (Universiti Malaysia Terengganu, 2009)

(untitled)
The decision on how to dispose municipal solid waste (MSW) is debatable, since there are many uncertain variables, Currently, this issue is discussed deeply among researchers and practitioners worldwide. This paper focuses on the development of the new multi-criteria decision-making (MCDM) approach with emphasizes on the various types of the input data in the evaluation process. By utilising both the analytic hierarchy process and fuzzy ideal solution method, the use of concentration and dilation concept was fully employed in the proposed method. The fundamental theory is briefly discussed to formulate the existing problem inline with the present dilemma of solid waste disposal. Validation through a case study was employed to demonstrate the applicability of the proposed method. The results showed that the model offers a versatile judgement, is clear in procedures and is successful in dealing with situations of diversified and too ill-defined in terms of input data. Moreover, it deals efficiently with the uncertainty ofthe initial information and facilitates systematic decision making.